Search for down-type fourth generation quarks with the ATLAS detector in events with one lepton and hadronically decaying W bosons. - Aad, G; Abbott, B; Abdallah, J; Abdelalim, A; Abdesselam, A; Abdinov, O; Abi, B; Abolins, M; AbouZeid, O; Abramowicz, H; Abreu, H; Acerbi, E; et al. (2012)
This Letter presents a search for pair production of heavy down-type quarks decaying via b' → Wt in the lepton + jets channel, as b'b' → W- tW+ t → bbW+ W- W+ W- → l± νbbqqqqqq. In addition to requiring exactly one lepton, large missing transverse momentum, and at least six jets, the invariant mass of nearby jet pairs is used to identify high transverse momentum W bosons. In data corresponding to an integrated luminosity of 1.04  fb(-1) from pp collisions at sqrt[s] = 7  TeV recorded with the ATLAS detector, a heavy down-type quark with mass less than 480 GeV can be excluded at the 95% confidence level.